Fractional Order Controller For Power Control in AC Islanded PV Microgrid using Electric Vehicles - Rafia, Anisha A. N.; Jayaprakash, Ramprabhakar (Recent Advances in Electrical & Electronic Engineering, 2024)
Background: Microgrids conquer a significant role in the evolution of distributed and modern grids from the traditional electricity system. However, microgrids with renewable energy sources connected to them often incur grid instability issues, due to the intermittent nature of these sources. Objective: This work aims to study Microgrids with Electric vehicles as a backup energy source and maintain the system’s frequency that can overcome this issue. Methods: This paper uses an autonomous control algorithm in an islanded ac microgrid to regulate the active power depending on the irradiation and load scenarios, thereby maintaining the system frequency and stability. The controller also keeps track of the battery's charge level, keeping it from overcharging or over-discharging conditions. The PI (Proportional Integral) and Fractional Order Proportional Integral (FOPI) controllers were compared, with the best controller utilized for system simulations. Results: Simulations are presented with MATLAB/Simulink for an Islanded Photo Voltaic AC microgrid system with the electric vehicle's battery connected to it as a source of backup energy. The system's effect is exhibited under varied irradiations and load levels, and the findings demonstrate the control algorithm's adaptability. Conclusion: This work attempts to discover the capability of the control technique to maintaining the stability of an AC islanded microgrid system under diverse irradiation and load situations, thereby maintaining the system's frequency and the State of Charge (SoC) of the battery of an electric vehicle under specified levels.
Keywords: fopid